2020
DOI: 10.1002/advs.202002142
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Porous Materials and Their Composites for NH3 Gas Removal

Abstract: NH 3 , essential for producing artificial fertilizers and several military and commercial products, is being produced at a large scale to satisfy increasing demands. The inevitable leakage of NH 3 during its utilization, even in trace concentrations, poses significant environmental and health risks because of its highly toxic and reactive nature. Although numerous techniques have been developed for the removal of atmospheric NH 3 , conventional NH 3 abatement systems possess the disadvantages of high maintenan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(51 citation statements)
references
References 126 publications
0
51
0
Order By: Relevance
“…This result correlates with the EDS result that the N compounds after and before adsorption do not show significant differences. The NH3 adsorption may be affected by several factors such as surface functional group, pore size and structure, and surface area (Kang et al, 2020;Yeom and Kim, 2017). Suspected in this study, acidic oxygen functional groups such as -OH, -NH, -C=O, -COOH, and metal ions is the main factor affecting adsorption capacity (Ro et al, 2015;Kang et al, 2020).…”
Section: Adsorption Capacitymentioning
confidence: 79%
“…This result correlates with the EDS result that the N compounds after and before adsorption do not show significant differences. The NH3 adsorption may be affected by several factors such as surface functional group, pore size and structure, and surface area (Kang et al, 2020;Yeom and Kim, 2017). Suspected in this study, acidic oxygen functional groups such as -OH, -NH, -C=O, -COOH, and metal ions is the main factor affecting adsorption capacity (Ro et al, 2015;Kang et al, 2020).…”
Section: Adsorption Capacitymentioning
confidence: 79%
“…The adsorption capacity of NH 3 is about 5 times higher than that of CO 2 at 298 K and is comparable to those found for other MOFs. 58 The strong adsorption capability of MDAF-4Dy toward ammonia may be explained by favourable interaction between alkaline NH 3 and acidic P-OH on the channel walls, which is supported by the significant hysteresis of the ammonia adsorption/desorption isotherm. After desorption, there remained 68.31 cm 3 g À1 (5.22 mol mol À1 ) of ammonia at P/P 0 = 0.001.…”
Section: Gas Sorption Propertiesmentioning
confidence: 87%
“…The adsorption of gaseous NH 3 onto zeolite is different from NH 4 + because NH 3 is a neutral molecule, and thus is physically bonded [ 24 ]. Some authors reported the development of porous NH 3 adsorbents with organic parts [ 25 ]. However, natural zeolites are inexpensive, widespread materials that are more appropriate for large-scale utilization, and considering the similarities of the chemical behavior of NH 3 and H 2 O molecules and the good adsorption capacity of water by zeolites, the suitability of zeolite clinoptilolite as NH 3 adsorbent can be supposed.…”
Section: Introductionmentioning
confidence: 99%